2016
DOI: 10.1080/01694243.2016.1162460
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of indirect composite onlays and overlays: 2-year follow up

Abstract: This prospective clinical trial evaluated the clinical performance of indirect onlay and overlay restorations made of resin composite. From January 2012 to March 2013, a total of 60 patients (36 males, 24 females; mean age; 34.4±10 years) received 67 posterior onlay/overlay restorations in the maxila or mandible made of laboratory processed indirect composite (Gradia, GC, Japan). Patients were followed until March 2015. Two operators luted all restorations adhesively (Variolink II). Two independent calibrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Eight full text articles were selected using electronic databases and 20 further were retrieved throughout manual search. From the 25 studies included in the meta-analysis, 12 studies were randomized controlled trial, 14 prospective and 2 retrospectives (Krejci et al 1992; Taskonak et al 2006; Frankenberger et al 2008; Frankenberger et al 2009; Dukic et al 2010; Fasbinder et al 2010; Manhart et al 2010; Azevedo et al 2012; Esuivel-Opshaw et al 2012; Murgueitio et al 2012; Schenke et al 2012; Taschner et al 2012; Gehrt et al 2013; Reich et al 2013; Akin et al 2014; D’all’Orologio et al 2014; Dhima et al 2014; Guess et al 2014; Guess et al 2014; Selz et al 2014; Seydler et al 2015; Baader et al 2016; Botto et al 2016; Mittal et al 2016; Özsoy et al 2016; Santos et al 2016; Rauch et al 2018) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight full text articles were selected using electronic databases and 20 further were retrieved throughout manual search. From the 25 studies included in the meta-analysis, 12 studies were randomized controlled trial, 14 prospective and 2 retrospectives (Krejci et al 1992; Taskonak et al 2006; Frankenberger et al 2008; Frankenberger et al 2009; Dukic et al 2010; Fasbinder et al 2010; Manhart et al 2010; Azevedo et al 2012; Esuivel-Opshaw et al 2012; Murgueitio et al 2012; Schenke et al 2012; Taschner et al 2012; Gehrt et al 2013; Reich et al 2013; Akin et al 2014; D’all’Orologio et al 2014; Dhima et al 2014; Guess et al 2014; Guess et al 2014; Selz et al 2014; Seydler et al 2015; Baader et al 2016; Botto et al 2016; Mittal et al 2016; Özsoy et al 2016; Santos et al 2016; Rauch et al 2018) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…From many studies, it has been found that this material has very good physicomechanical properties, such as high strength, wear-resistance, and superior polishability for such restorations. 10,22,23 In this clinical study, at the 3-year and 6-year follow-up, the success rate of the restorations was 100% without failure. At a 9-year follow-up, the success rate was 85% and the failure rate was 15%.…”
Section: Discussionmentioning
confidence: 58%
“…From many studies, it has been found that this material has very good physicomechanical properties, such as high strength, wear-resistance, and superior polishability for such restorations. 10 22 23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations